2018
DOI: 10.3390/nu10101561
|View full text |Cite
|
Sign up to set email alerts
|

Polyunsaturated Fatty Acids and Their Potential Therapeutic Role in Cardiovascular System Disorders—A Review

Abstract: Cardiovascular diseases are described as the leading cause of morbidity and mortality in modern societies. Therefore, the importance of cardiovascular diseases prevention is widely reflected in the increasing number of reports on the topic among the key scientific research efforts of the recent period. The importance of essential fatty acids (EFAs) has been recognized in the fields of cardiac science and cardiac medicine, with the significant effects of various fatty acids having been confirmed by experimental… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
169
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 270 publications
(189 citation statements)
references
References 139 publications
1
169
0
Order By: Relevance
“…The bacteria recently been characterized from Tropical gar fish (Atractosteus tropicus) where its positive role on fish adaptation and survival has been described 62 . Paracoccus species identified from turbot (Scophthalmus maximus), European flounder (Platichthys flesus) and wild common dab (Limanda limanda) gut were found strongly correlated to high content of polyunsaturated fatty acids (PUFA), especially docosahexaenoic acid (DHA) and eicosapentaenoic acid (EPA) that have potential health benefit effects on aquatic animals as well as on humans, especially the role of PUFA in liver and brain function, inflammation, cardiovascular diseases, obesity and diabetes has been widely documented [63][64][65] . Another genus Luteolibacter is described to play a positive role in Lactobacillus colonization in the fish gut, however, the mechanism is not clearly stated yet 66,67 .…”
Section: Discussionmentioning
confidence: 99%
“…The bacteria recently been characterized from Tropical gar fish (Atractosteus tropicus) where its positive role on fish adaptation and survival has been described 62 . Paracoccus species identified from turbot (Scophthalmus maximus), European flounder (Platichthys flesus) and wild common dab (Limanda limanda) gut were found strongly correlated to high content of polyunsaturated fatty acids (PUFA), especially docosahexaenoic acid (DHA) and eicosapentaenoic acid (EPA) that have potential health benefit effects on aquatic animals as well as on humans, especially the role of PUFA in liver and brain function, inflammation, cardiovascular diseases, obesity and diabetes has been widely documented [63][64][65] . Another genus Luteolibacter is described to play a positive role in Lactobacillus colonization in the fish gut, however, the mechanism is not clearly stated yet 66,67 .…”
Section: Discussionmentioning
confidence: 99%
“…35 The PUFAs are considered to be anticholesterolemic, although their beneficial effects depend on the ratio of omega 6 (n-6) to omega 3 (n-3) fatty acids. 36,37 In this regard, t, his ratio is different depending on the area being considered the n-6/n-3 ratios varied between 4 (Japan) and 38-50 (India), whilst Europe and US present generally intermediate levels, being 15 and 16.74, respectively. 38 Overall, when considering the individual fatty acid composition of the re-formulated sausages (i.e., Carrot 10, Carrot 20, and Carrot 30) (Table 4), we observed an abundance of oleic acid (C18:1n-9; on average: 35.25%), followed by palmitic acid (C16:0; on average: 23.02%), linoleic acid (C18:2n-6; on average: 19.69%), stearic acid (C18:0; on average: 7.08%), and palmitoleic acid (C16:1n-7; on average: 5.74%).…”
Section: Effect Of Carrot Addition On the Fatty Acid Profile Of Freshmentioning
confidence: 99%
“…These authors report that the AI and TI highlight the importance of unsaturated lipids for addressing issues resulting from the excessive intake of saturated lipids. All UFA with one or several double bonds contribute to decreasing these indices, indicating the potential stimulation of platelet aggregation, that is, the lower these values are, the higher the amount of anti-atherogenic fatty acids present in a specific fat tissue and the lower the potential to prevent the onset of coronary heart disease (Aguiar et al, 2017;Sokoła-Wysoczanska, 2018). In the present study, the subcutaneous fat showed a significantly lower (p < 0.05) TI, followed by the intramuscular and intermuscular fat.…”
Section: Relationship Between Fatty Acids Obtained and Risk Factorsmentioning
confidence: 99%